Total Synthesis of Natural Products Using Intramolecular Nozaki–Hiyama–Takai–Kishi Reactions - Takao, Ken-ichi; Ogura, Akihiro; Yoshida, Keisuke; Simizu, Siro (Synlett, 2020)
In this Account, we describe our studies on the total synthesis of several natural products using intramolecular Nozaki–Hiyama–Takai–Kishi (NHTK) reactions. In each synthesis, an NHTK reaction is used to efficiently construct a medium-sized ring. These examples demonstrate the utility of the intramolecular NHTK reaction in natural product synthesis.1 Introduction2 Total Synthesis of (+)-Pestalotiopsin A3 Total Synthesis of (+)-Cytosporolide A4 Total Synthesis of (+)-Vibsanin A5 Total Syntheses of (+)-Aquatolide and Related Humulanolides6 Conclusion
Keywords: total synthesis; cyclization; medium-sized rings; all-carbon quaternary stereocenters; cycloaddition; metathesis